A single switch DC/DC converter with galvanic isolation and input current regulation for photovoltaic systems. (September 2015) - Tsang, K.M.; Chan, W.L.
Highlights: Novel single switch converter with galvanic isolation. Input current regulation for maximum power point tracking. Low cost and high conversion efficient could be achieved. Abstract: This paper presents a novel high power single switch DC/DC converter with galvanic isolation for photovoltaic (PV) systems. The converter input current and output voltage can both be regulated independently based on the operation of a single switch. The output voltage can be controlled based on the duty ratio of the electronic switch and is no longer determined by the turn ration of the isolation transformer. With the proposed configuration and switching action, the average magnetic flux within the transformer core over one switching cycle is zero and hence a full switching cycle can be used for high power transfer. A fast current controller is also developed for the proposed converter such that maximum power point tracking (MPPT) algorithm based on PV panel output current can be developed. Moreover, MPPT based on a triangular reference input current is implemented. Experimental results are included to demonstrate the effectiveness of the proposed converter and control scheme.